Insights: elucidation of squalene monooxygenase inhibitors for lowering cholesterol in cardiovascular diseases - Leoma, Mofeli Benedict (Rhodes University, Faculty of Science, Department of Chemistry)
Statins have been used to lower high cholesterol levels in the past few decades. However, several studies have shown that some people taking statins experience side effects over time, especially elderly patients, women of childbirth possibility, and children. Several studies have shown that the majority of people with underlying cardiovascular complications caused by high cholesterol are at a greater risk of fatality due to COVID-19, regardless of age and sex. The literature suggests that antimycotic squalene monooxygenase inhibitors, terbinafine and its derivatives, and anticholesterolemic squalene monooxygenase (SM) inhibitors could be another option and a safer remedy for lowering cholesterol in mammals. Molecular docking calculations, molecular dynamics (MD) simulations, molecular mechanics generalized born surface area (MM-GBSA) calculations, quantum mechanics/molecular mechanics calculations (QM/MM), and density functional theory (DFT) calculations were used in this study. An early stage in drug discovery, in which small molecular hits from high- throughput screening (HTS) are evaluated and undergo limited optimization to identify promising lead compounds, is referred to as lead generation. To address the first step of lead generation, the number of compounds to be tested was narrowed down, and the hit compounds that could be taken for further tests were obtained. Thus, the molecular docking technique was taken advantage of, which assisted us in identifying the antimycotic ligand SDZ 18, which had a good binding affinity of about -8,4 kcal molâˆ’1. Another widely employed strategy, the molecular mechanics-generalized born surface area (MM-GBSA), was used to investigate the binding free energies of the protein-ligand complexes to validate the binding affinities obtained from molecular docking. Despite the excellent docking results, it must be emphasized that the stability of the ligand in the binding pocket must be investigated. To address this, the protein-ligand complexes were then taken through molecular dynamics for 100 ns simulations calculations which showed that the inhibitors stayed in the binding pocket with the RMSD values below 3.5 Ã… for most systems. This provided insight into a realistic model because the docked complexes were placed in conditions closer to the physiological environment at 300 K and 1.01325 bar, and in an explicitly solvated dynamic environment. Density functional theory (DFT) at the B3LPY level of theory using the standard 6-31G(d,p) basis set was used to assess the reactivity and other properties of the SM inhibitors. ONIOM calculations were performed to explain what was happening at the microscopic level by calculating the total energy of the complex. The aim of this project was to efficiently uncover the non-physical aspects of SM inhibitors with the help of computational techniques to identify new drugs that can lower high cholesterol levels. From a theoretical perspective, the results obtained from docking indicated that the antimycotic ligands SDZ SBA 586 18 and TNSA 84 (trisnor-squalene alcohol ) have good binding affinities, and the MM-GBSA method provided free energy calculations. MD results indicated that the stability of the ligand in the binding pocket was achieved during the 100 ns simulations. The HOMO-LUMO energy gaps obtained from DFT calculations provided information on the reactivity of the ligands. Other insights into the protein-ligand complexes were obtained from a hybrid ONIOM QM/MM study.
Keywords: Squalene monooxygenase; Cholesterol; Cardiovascular system Diseases; Anticholesteremic agents; Molecular dynamics; High throughput screening (Drug development); Molecular Docking